Pembuatan Plastik Biodegradable Dari Pati Biji Nangka - Nuryati Nuryati; Jaka Darma Jaya; Norhekmah Norhekmah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2019)
Jackfruit seeds have not been widely used or thrown away as a waste. The content of jackfruit seeds in 100 gr contains 36,7 gr of carbohydrates, 4,2 gr of protein, 165 kcal of energy, so that it is used as food. Jackfruit seed starch isvery cheap even can bemade by itself simple. Relatively high starch contant of about 40-50%. The purpose of this research is to make biodegradable plastic from jackfruit seed starch with variation of glycerol addition, to know the result of biodegradable plastic from jackfruit seed starch. Method used in the study : making biodegradable plastic from jackfruit seed starch with variation of glycerol 2 ml, 3 ml dan 4ml. research was conducted by conducting water resistance test , melting poin test and biodegradable test. Results obtained from the research of making a better biodegradable plastic glycerol 2 ml because it can be seen plastik sheets of all smooth, thinner, clearer and transparent surfaces, no bubbles compared to other glycerol variations seen brownish. Water resistance test with the addition of 2 ml glycerol with the highest water endurance 91,67% with water absorption test using hot plate because the sample heating cannot melt perfectly and that can be observed only shrinkage. A biodegradable test 4 ml glycerol addition resulted a reduced percentage of residual weight of plastic increased by 78,57%.